Sustainable synthesis of pharmaceuticals : using transition metal complexes as catalysts - Calvete, Mário J. F.; Pereira, Mariette M. (RSC green chemistry series., 2018)
There is a growing interest in the development of sustainable processes for the synthesis of pharmaceuticals and this book bridges the divide between industrial examples and the fundamental chemistry. It explains the basic principles of using transition metal catalysis with several green approaches for the synthesis of pharmaceuticals. The topic is an important one for green chemistry and the chapters in this book on hydroformylation, green oxidation and olefin metathesis will also be of interest to both medicinal and organic chemists. Written by leading experts in the field, it provides a valuable and easy tool for scientists and industrialists who require information regarding this topic.